Optimal capacitor placement and sizing in radial electric powe - Ahmed Elsheikh; Yahya Helmy; Yasmine Abouelseoud; Ahmed Elsherif (Alexandria Engineering Journal, 2014)
The use of capacitors in power systems has many well-known benefits that include improvement of the system power factor, improvement of the system voltage profile, increasing the maximum flow through cables and transformers and reduction of losses due to the compensation of the reactive component of power flow. By decreasing the flow through cables, the systems’ loads can be increased without adding any new cables or overloading the existing cables. These benefits depend greatly on how capacitors are placed in the system. In this paper, the problem of how to optimally determine the locations to install capacitors and the sizes of capacitors to be installed in the buses of radial distribution systems is addressed. The proposed methodology uses loss sensitivity factors to identify the buses requiring compensation and then a discrete particle swarm optimization algorithm (PSO) is used to determine the sizes of the capacitors to be installed. The proposed algorithm deals directly with discrete nature of the design variables. The results obtained are superior to those reported in Prakash and Sydulu (2007).